Individual anaerobic threshold estimates maximal lactate steady state in temperate and hot climate - Monteiro de Barros, C. L.; Mendes, T. T.; de Avila Castro Fleury Mortimer, L.; Passos Ramos, G.; Silami Garcia, E. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The aim of the present study was to compare the power output at the maximal lactate steady state (MLSS) with the power output at the individual anaerobic threshold (IAT) and at the onset of blood lactate accumulation (OBLA) in both temperate (TEMP) (22 °C) and hot (HOT) (40 °C) climates. METHODS: Eight young active male (23.9±2.4 yr, 75.9±7.3 kg and 47.8±4.9 mL/kg/min) were evaluated on a cycle ergometer and performed a progressive exercise test until fatigue to determine the IAT and OBLA and two to five 30-min exercise tests at constant intensities for determine MLSS at both temperatures. An ANOVA with repeated measures and Dunnett`s post-hoc test was performed to compare results of IAT and OBLA to the variables at the MLSS in both climates with MLSS being considered as the standard. RESULTS: At TEMP there was no difference between the power output at MLSS and IAT (180±11 W and 182±13 W, respectively), however, the intensity of the OBLA (154±11 W) was lower than MLSS (PCONCLUSIONS: These results showed that IAT is sensitive enough to estimate MLSS in both TEMP and HOT climate.